The degree of educational supervisors' practice of conflict Management - algaraidih, mohamed suliman (Advances in Social Sciences Research Journal, 2019)
Abstract This study aims at highlighting the degree of educational supervisors' practice of conflict management strategies in AlDahra Governate in Oman. In order to achieve the goal, a questionnaire was conducted and that composed of (47) items distributed on seven key areas. After ensuring the validity and reliability of the questionnair, they were applied to (130) educational supervisors and first teachers. To answer the study questions, the study used means, standard deviations, and T-Test. The main results show that supervisors implement all conflict management strategies in AlDahra governate in Oman moderately and as the following Descending order: participation, settlement, avoidance, enforcement, and courtesy. Also, there are no statistically significant differences at the level of significance (α≤ 05,0) to practice the degree of educational supervisors' practice strategies for conflict management based on the variables of social status, qualification and years of experience. In the light of the results of the study, the researcher recommends the need of paying attention by the educational supervisors to understanding teachers’ attitudes, points of view, aspirations, and the involvement of some mediators in the event of problems between supervisors and teachers and between teachers themselves, employment of courtesy and diplomacy with teachers to end disputed issues, which reduces the chances of future conflict and being supporter to solutions between the parties of possible conflict. Keywords: educational supervisors, practice, conflict Management strategies.